Individual Educational Paths in the Universities of Russia and Great Britain (Theoretical Aspects) - N. Yu. Shaposhnikova (Vestnik MGIMO-Universiteta)
The author highlights the necessity for higher education institutions to form and realize students' individual educational paths in the learning process, which is stated in the Federal Law on Education and FSES HPE of the third generation. The article presents an overview of the different approaches to the definition of the term «individual educational path» (IEP). It also gives a brief overview of the existing terms in the Russian terminological system, which are close in meaning to the term above. The author formulates her own tentative definition of the term «IEP» which is based on the analysis made. The article further addresses the solution to the problem of the individualization of higher education learning process in Great Britain, which is described through the term «Personal Development Planning». The meaning of the term is shown through the set of actions: planning, doing things, recording of the self experience, reviewing and evaluating, using the personal knowledge derived from reflection and self understanding as well as own learning abilities to plan future actions. In conclusion, the meanings of the terms «IEP» and «PDP» are compared. The author emphasires the importance of studying Great Britain's experience - the practice of solving problems connected with the individualization of the university learning process and the possibilities to use it to facilitate the implementation of students' individual educational paths in Russian higher education institutions.